T=16x2y2+y2z2+z2x2+1+x2y2+y2z2+z2x2+1+xy+yz+zx+1x+y+z−1−x2y2−y2z2−z2x2−1≥8−1+xy+yz+zx+1x+y+z−1−x2y2−y2z2−z2x2Mà theo Bunhia-Copxki: (1+1+1)(x2+y2+z2)≥(x+y+z)2⇔9≥(x+y+z)2⇒x+y+z≤3$$\Rightarrow T\geq 7+\frac{xy+yz+zx+1}{2}-x^2y^2-y^2z^2-z^2x^2Cầnchứngminh:6\leq7+\frac{xy+yz+zx+1}{2}-x^2y^2-y^2z^2-z^2x^2⇔2(x2y2+y2z2+z2x2)≤xy+yz+zx+3\Leftrightarrow 2(x^2y^2+y^2z^2+z^2x^2+2xy+2yz+2zx) \geq 5(xy+yz+zx)+3⇔(xy+yz+zx)2≤5(xy+yz+zx)+3\Leftrightarrow (xy+yz+zx)^2-5(xy+yz+zx)-3\leq 0$$\Leftrightarrow (xy+yz+zx-3)(2xy+2yz+2zx+1)\leq0$Vì $xy+yz+zx\leq x^2+y^2+z^2=3$Nên $(xy+yz+zx-3)(2xy+2yz+2zx+1)\leq0$Nên, bất đẳng thức cần chứng minh luôn đúng với $x,y,z$ thỏa mãn điều kiện đề bài.Vậy, $T\geq6 \Leftrightarrow x=y=z=1$
T=16x2y2+y2z2+z2x2+1+x2y2+y2z2+z2x2+1+xy+yz+zx+1x+y+z−1−x2y2−y2z2−z2x2−1≥8−1+xy+yz+zx+1x+y+z−1−x2y2−y2z2−z2x2Mà theo Bunhia-Copxki:
(1+1+1)(x2+y2+z2)≥(x+y+z)2⇔9≥(x+y+z)2⇒x+y+z≤3⇒T≥7+xy+yz+zx+12−x2y2−y2z2−z2x2Cần chứng minh:
6≤7+xy+yz+zx+12−x2y2−y2z2−z2x2⇔2(x2y2+y2z2+z2x2)≤xy+yz+zx+3⇔2(x2y2+y2z2+z2x2+2xy+2yz+2zx)≥5(xy+yz+zx)+3⇔(xy+yz+zx)2≤5(xy+yz+zx)+3⇔(xy+yz+zx)2−5(xy+yz+zx)−3≤0⇔(xy+yz+zx−3)(2xy+2yz+2zx+1)≤0Vì
xy+yz+zx≤x2+y2+z2=3Nên
(xy+yz+zx−3)(2xy+2yz+2zx+1)≤0Nên, bất đẳng thức cần chứng minh luôn đúng với
x,y,z thỏa mãn điều kiện đề bài.Vậy,
T≥6⇔x=y=z=1